Effects of Mycorrhizal Colonization on Transcriptional Expression of the Responsive Factor JERF3 and Stress-Responsive Genes in Banana Plantlets in Response to Combined Biotic and Abiotic Stresses - Rashad, Younes M.; Fekry, Waleed M. E.; Sleem, Mohamed M.; Elazab, Nahla T. (Frontiers in Plant Science, 2021)
Banana (Musa acuminata L.) is exposed to various biotic and abiotic stresses that affect its production worldwide. Banana plants respond to these stresses, but their responses to combined stresses are unique and differ from those to various individual stresses. This paper reported effects of mycorrhizal colonization of banana roots and/or infection with root rot on the transcriptional expression of the responsive factor JERF3 and stress-responsive genes (POD, PR1, CHI, and GLU) under different salinity levels. Different transcriptional levels were recorded in response to the individual, dual or triple treatments. All the applied biotic and abiotic stresses triggered the transcriptional expression of the tested genes, when individually applied, but they showed different influences varying from synergistic to antagonistic when applied in combinations. The salinity stress had the strongest effect when applied in combination with the biotic stress and/or mycorrhizal colonization, especially at the high concentration Moreover, the salinity level differentially affects banana responses under combined stresses and/or mycorrhizal colonization In addition, mycorrhizal colonization of banana plantlets improved their growth, photosynthesis, and nutrient uptake, as well as greatly alleviated the detrimental effects of the salt and infection stresses. In general, the obtained results indicated that responses of banana plantlets under the combined stresses are more complicated and differed from those under the individual stresses depending on the crosstalks between the signaling pathways.